Characterization and functional analysis of the proteins Prohibitin 1 and 2 in Trypanosoma cruzi. - Ana K Ibarrola-Vannucci; Luis M De Pablos; Lissette Retana-Moreira; Alberto Cornet-Gomez; Teresa Cruz-Bustos; Alejandro G Schijman; José L Ramírez; Susana Vílchez; Antonio Osuna (Public Library of Science (PLoS), 2021)
Background Chagas disease is the third most important neglected tropical disease. There is no vaccine available, and only two drugs are generally prescribed for the treatment, both of which with a wide range of side effects. Our study of T. cruzi PHBs revealed a pleiotropic function in different stages of the parasite, participating actively in the transformation of the non-infective replicative epimastigote form into metacyclic trypomastigotes and also in the multiplication of intracellular amastigotes. Methodology/principal findings To obtain and confirm our results, we applied several tools and techniques such as electron microscopy, immuno-electron microscopy, bioinformatics analysis and molecular biology. We transfected T. cruzi clones with the PHB genes, in order to overexpress the proteins and performed a CRISPR/Cas9 disruption to obtain partially silenced PHB1 parasites or completely silenced PHB2 parasites. The function of these proteins was also studied in the biology of the parasite, specifically in the transformation rate from non-infective forms to the metacyclic infective forms, and in their capacity of intracellular multiplication. Conclusion/significance This research expands our understanding of the functions of PHBs in the life cycle of the parasite. It also highlights the protective role of prohibitins against ROS and reveals that the absence of PHB2 has a lethal effect on the parasite, a fact that could support the consideration of this protein as a possible target for therapeutic action.